2014
DOI: 10.1002/iub.1278
|View full text |Cite
|
Sign up to set email alerts
|

Selection and evolution of resistance to antimicrobial drugs

Abstract: The overuse and misuse of antibiotics over many years has selected a high frequency of resistance among medically important bacterial pathogens. The evolution of resistance is complex, frequently involving multiple genetic alterations that minimize biological fitness costs and/or increase the resistance level. Resistance is selected at very low drug concentrations, such as found widely distributed in the environment, and this selects for resistant mutants with a high fitness. Once resistance with high fitness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…A phenomenon of selection of streptomycin‐resistant strains could have influenced the higher frequency and persistence of strains of ST32 between Chilean Cmm strains studied. Hughes () discussed how bacteria respond to the selective pressure upon antibiotic exposure. Antibiotic usage over many years has selected a high frequency of resistant strains among clinically relevant bacterial pathogens, and once resistant strains with high fitness are established in a bacterial community, it is very difficult to reduce their resistance frequency.…”
Section: Discussionmentioning
confidence: 99%
“…A phenomenon of selection of streptomycin‐resistant strains could have influenced the higher frequency and persistence of strains of ST32 between Chilean Cmm strains studied. Hughes () discussed how bacteria respond to the selective pressure upon antibiotic exposure. Antibiotic usage over many years has selected a high frequency of resistant strains among clinically relevant bacterial pathogens, and once resistant strains with high fitness are established in a bacterial community, it is very difficult to reduce their resistance frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance is one of the greatest threats to global public health and the World Health Organisation warns against a return to a pre-antibiotic era [1]. Higher prevalence of resistance among human pathogens increases the risk of uncontainable infections, prolonged illness and hospital stay, increased mortality, and consequently increased health care costs [2]. Antibiotic use is the main driver of antibiotic resistance, why addressing the excessive and inappropriate use of antibiotics is essential [3].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is important to consider potential alterations in the fitness of MDROs in causing persistent colonization or infection. Although mutations that lead to antibiotic resistance may result in reduced fitness, studies have shown that additional mutations over time may compensate for these fitness costs and that MDROs can subsequently become even more virulent even in settings free of antimicrobials (12)(13)(14)(15).…”
mentioning
confidence: 99%